Expanding Banking Services to Micro, Small and Medium Enterprises and Poor Households in the Philippines - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 2001)
This paper has reviewed existing policies and programs to encourage banks to expand their financial services to micro, small- and medium-sized enterprises (MicSMEs) and poor households. The overall policy environment for promoting microfinance in the Philippines has indeed considerably improved since 1990, and there are signs that banks have favorably responded to it. However, banks still face some constraints in expanding further their financial services to MicSMEs and poor households. This paper has discussed these constraints and recommended some measures to overcome them.
Keywords: 330; microfinance; poverty; credit program; microenterprises; small and medium enterprises (SMEs); Kreditgeschäft; KMU; Niedrigeinkommen; Philippinen; Mikrofinanzierung